Exploring Pedagogical Challenges Faced by EFL Teacher Candidates: A Qualitative Analysis in the English Laboratory - Rahmawati, Widya; Puspitasari, Ema; Karim, Samuel; Fahmi, Fahmi (Madiha Press, 2025)
Abstract Teacher candidates play a strategic role in ensuring the quality of future educational systems, yet many continue to encounter significant challenges during their teaching practicum, particularly related to pedagogical competence. This study investigates the pedagogical obstacles faced by EFL teacher candidates during their teaching performance in the English Laboratory of Muhammadiyah University of Metro. Using a descriptive qualitative design, data were collected through observation, interviews, and document analysis involving 12 assistants and 5 key informants. The findings reveal that teacher candidates commonly struggle with selecting appropriate teaching methods, managing students’ diverse learning abilities, and utilizing instructional media effectively. Moreover, the mismatch between chosen teaching strategies and students’ learning conditions often leads to ineffective learning processes. This study highlights the importance of strengthening pedagogical competence, including mastery of teaching methods, classroom management, and instructional media integration, to improve the teaching readiness of future teachers. The implications emphasize the need for more comprehensive pedagogical training and ongoing mentorship during teaching practicum programs.